2005
DOI: 10.1513/pats.200504-040sr
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids: Potential  2-Agonist and Anticholinergic Interactions in Chronic Obstructive Pulmonary Disease

Abstract: Corticosteroids are often used in combination with beta2-agonist and anticholinergic bronchodilators in the treatment of chronic obstructive pulmonary disease (COPD). Corticosteroids activate the beta2-receptor gene, increasing receptor number and decreasing desensitization. Long-acting beta2-agonists prime the glucocorticoid receptor and enhance nuclear translocation via activation of CCAAT enhancer binding protein-alpha. Corticosteroids can also increase prejunctional auto-inhibitory M2-receptor gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
19
1
1
Order By: Relevance
“…␤2-agonists and/or anticholinergic bronchodilators and corticosteroids are often used in combination in the treatment of COPD patients (Johnson, 2005). Tiotropium is a once-daily inhaled anticholinergic bronchodilator commonly used in the treatment of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…␤2-agonists and/or anticholinergic bronchodilators and corticosteroids are often used in combination in the treatment of COPD patients (Johnson, 2005). Tiotropium is a once-daily inhaled anticholinergic bronchodilator commonly used in the treatment of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…As recommended by Global Initiative for Asthma (GINA) guideline, LABA should not be used as monotherapy in asthma, because ICS has been reported to not only suppress airway inflammation and hyperreactivity, however, it also prevent LABA induced down-regulation of β 2 AR and recover their sensitivity, thus may lead to increase of M 3 R, PLC-β 1 , and IP 3 expression as demonstrated by McGraw943. On contrary, recent studies found that steroids could decrease the expression of muscarinic receptor and PDE4 mRNA in airway smooth muscle, which may result in bronchoprotection28434445.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] This combination of salmeterol and FP (SFC) has demonstrated a broad range of anti-inflammatory effects 10 that are greater than those seen with inhaled corticosteroid (ICS) monotherapy 11 and the likely explanation for this is a molecular interaction (synergy) between the LABA and ICS. 12 The anti-inflammatory and bronchodilator effects of SFC provides greater symptom control, pulmonary function improvement and exacerbation reduction compared with either of the individual component treatments. 9 Current COPD guidelines recommend that long acting bronchodilators should be used in patients who are symptomatic despite therapy with short acting bronchodilators.…”
mentioning
confidence: 99%